Synthesis of WS2 by Chemical Vapor Deposition: Role of the Alumina Crucible - Neileth Stand; Cesar D. Mendoza; Fernando L. Freire (Crystals, 2022)
The role of the alumina crucible for the tungsten disulfide (WS2) growth on silicon dioxide substrates (SiO2/Si) under atmospheric pressure chemical vapor deposition (APCVD) was investigated. Both synthesis and properties of the APCVD-WS2 depend on the number of growth cycles when using the same alumina crucible. It was discovered that there is an ideal condition for the material’s synthesis, which is characterized by an increase in the photoluminescence (PL) yield and larger WS2 triangles. It usually happens for the first three growth cycles. For the fourth cycle and beyond, the PL decreases gradually. Simultaneously, atomic force microscopy images revealed no important changes in the topography of the WS2 flakes. As a function of the number of synthesis cycles, the progressive decrease in PL yield could be associated with materials with a higher density of defects, as identified by the LA(M)/A1g(M)−LA(M) ratio from Raman data using the green line.